Statistics the art and science of learning from data - Agresti, Alan; Franklin, Christine A. (Pearson Education, 2014)
This book helps students become statistically literate by encouraging them to ask and answer interesting statistical questions. The Third Edition has been edited for conciseness and clarity to keep students focused on the main concepts.